Ties of the Diaspora of Lithuanian Origin in Kazakhstan with Lithuanian ethnic identity and the Lithuanian language - Vilkienė, Loreta (Taikomoji kalbotyra, 2023)
This article focuses on the diasporas of Lithuanian Origin in Kazakhstan and their links with Lithuanian ethnic identity and the Lithuanian language. This research aims to answer the question of what strategies were chosen by three generations of the target diaspora to maintain Lithuanian identity and the Lithuanian language. Also, the paper is exploring the reasons that encouraged specific decisions and behavior of the target diaspora. The research material was 38 qualitative semi-structured interviews collected in November 2021 during the expedition in Kazakhstan. The interviews were qualitatively analysed using the adapted Bamberg’s (2011) Narrative Practice and Identity Navigation model. The analysis of the case of the diaspora of Lithuanian origin in Kazakhstan revealed that three generations of the diaspora have preserved their Lithuanian ethnic identity and expressed favorable attitudes towards Lithuanianness, Lithuania, and Lithuanians. However, the Lithuanian language, which is not necessarily considered part of the ethnic identity of the target group, was not maintained. It can be said that the second generation does not know the Lithuanian language. However, the third generation shows a more active relationship with the Lithuanian language and wants to learn it. There are various reasons why the Lithuanian language is not being passed down to the next generations, namely: 1) the consequences of social trauma, such as the abandonment of the first generation’s language as a survival strategy; state policies promoting Russification; 2) the formation of mixed families of deportees, 3) conflicts between the first generation and their relatives in Lithuania, the broken contacts reduced the possibilities of communication in Lithuanian; lack of available Lithuanian-speaking individuals to communicate with, as there are no larger Lithuanian communities; 4) the pursuit of economic prosperity and integration, particularly for those who voluntarily migrated to Kazakhstan, etc.
Keywords: Diaspora of Lithuanian Origin in Kazakhstan; ethnic identity; the Lithuanian language; identity navigation model